2020
DOI: 10.3390/molecules25102390
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Different Artemisia Essential Oil Formulations

Abstract: The extreme lipophilicity of essential oils (EOs) impedes the measurement of their biological actions in an aqueous environment. We formulated oil in water type Pickering Artemisia annua EO nanoemulsions (AEP) with surface-modified Stöber silica nanoparticles (20 nm) as the stabilizing agent. The antimicrobial activity of AEP and its effects on mature Candida biofilms were compared with those of Tween 80 stabilized emulsion (AET) and ethanolic solution (AEE) of the Artemisia EO. The antimicrobial activity was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 48 publications
(90 reference statements)
0
25
0
Order By: Relevance
“…On the other hand, quantification is possible in Selected Ion Monitoring (SIM) mode, with selected ions calibrated with external standards. In this work, all samples were analyzed by GC-MS for compound identification, and FID for reliable peak quantification [ 34 , 35 ]. Figure 3 reports the GC-MS chromatograms of the volatile content of leaves of the three Brassica cultivars investigated, collected at the edible salad phase, when plants are about 15–20 cm high, while Table 3 reports the correspondent quantitative determination by GC-FID.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, quantification is possible in Selected Ion Monitoring (SIM) mode, with selected ions calibrated with external standards. In this work, all samples were analyzed by GC-MS for compound identification, and FID for reliable peak quantification [ 34 , 35 ]. Figure 3 reports the GC-MS chromatograms of the volatile content of leaves of the three Brassica cultivars investigated, collected at the edible salad phase, when plants are about 15–20 cm high, while Table 3 reports the correspondent quantitative determination by GC-FID.…”
Section: Resultsmentioning
confidence: 99%
“…EOs from different Artemisia species are well documented for their antimicrobial activity and several investigations have reported that they displayed remarkable antibacterial and antifungal activities against several microbial strains [ 51 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…It involves the hydrolysis and condensation of the alkoxide monomers into a colloidal solution that acts as a precursor to form an ordered gel-like network of polymer or discrete particles, in the presence of an acid or a base catalyst. Another modification of this process involves use of a cationic surfactant in the reaction mixture resulting in spherical particle of submicrometer size monodisperse particles [ 111 ]. Silica nanoparticles loaded with essential oils of chamomile, Artemisia annua , lemongrass and clove, peppermint, Pistacia atlantica were formulated by this method with particle sizes ranging from 20 nm to 500 nm.…”
Section: Synthesis Of Essential Oil-loaded Nanoparticlesmentioning
confidence: 99%
“…The AEP showed significant antibacterial and antifungal activities (MIC 90 ) on Escherichia coli (1.68 ± 0.72 µg/mL), Staphylococcus aureus (1.62 ± 0.37 µg/mL), B. subtilis (1.42 ± 0.64 µg/mL), P. aeruginosa (1.46 ± 0.22 µg/mL), S. pyogenes (3.15 ± 0.16 µg/mL), S. pombe (2.01 ± 0.46 µg/mL), C. albicans (3.62 ± 0.65 µg/mL), C. tropicalis (4.29 ± 0.82 µg/mL), C. dubliniensis (3.63 ± 0.57 µg/mL) and C. krusei (3.79 ± 0.57 µg/mL), respectively, in comparison to AET. AEP demonstrated superior antibacterial efficacy at an average of twelve-fold less concentration in comparison to AEE [ 111 ]. Satary et al developed lemongrass and clove Eos that were encapsulated into mesoporous silica nanoparticles (LGO-MSNPs and CO-MSNPs) coated with alginate using the sol–gel method to combat Gaeumannomyces graminis , causative organism of wheat take all disease.…”
Section: Nanoparticles As Carriers Of Eomentioning
confidence: 99%